Maternal amylase, lipase, lactate dehydrogenase, creatine kinase levels at preterm delivery, and the effect of tocolysis - Genç, Simten; Eren, Melike; Kükrer, Sadık; Yurci, Arzu; Cıngıllıoğlu, Başak; Köse, Elif Dilasa; Sahın, Orhan; Şirinoğlu, Hicran; Mihmanlı, Veli (Journal of Surgery and Medicine, 2021)
Background/Aim: Preterm labor is one of the main obstetric problems and the leading cause of neonatal mortality and morbidity. Some pregnant women at risk of preterm labor receive tocolytic therapy, but the agents used can affect maternal blood parameters and enzyme levels. Physiological changes that occur during pregnancy may cause changes in enzymatic activities. Maternal amylase, lipase, lactate dehydrogenase (LDH), and creatine kinase (CK) levels should be followed throughout pregnancy to assess any increase. This study aimed to examine maternal amylase, lipase, creatine kinase, and lactate dehydrogenase levels in pregnant women who gave term and preterm birth and determine the physiological changes that may occur with gestational age and tocolysis. Methods: The records of patients over their 24th gestational week who gave birth at the Gynecology and Obstetrics Department of Okmeydani Training and Research Hospital between July-December 2018 were reviewed in this retrospective cohort study. Their clinical findings, maternal and obstetric outcomes were noted. A total of 548 pregnant women were included in the study, who were divided into three groups: Group 1- Preterm delivery without tocolysis, Group 2- Preterm delivery with tocolysis, Group 3- Term delivery Results: The maternal age, gravidity, history of abortion, fetal gender, amylase, and lipase values were similar between the groups (p>0.05 for all), while delivery types and cesarean section indications significantly differed (p=0.009, and p<0.001 respectively). The mean LDH value of Group 2 was significantly higher than those of Groups 1 and 3 (p=0.006, and p=0.024, respectively). The mean CK value of Group 3 was also higher than those of Groups 1 and 2 (p=0.021, and p<0.001, respectively), and that of Group 1 was significantly higher than that of Group 2 (p=0.021). LDH, amylase, lipase, and CK levels were not correlated with gestational age and fetal weight in the premature birth groups. In Group 3, a significant negative correlation was observed between fetal weight and amylase (r = -0.136 P=0.02). Among all patients, gestational week and LDH (r = -0.117, P=0.006) and fetal weight and LDH (r = -0.107, P=0.012) were negatively correlated, while fetal weight and lipase (r = 0.095 P=0.027) and gestational week and CK were positively correlated (r = 0.085 P=0.047) (Table 2, Figures 2 and 3). Conclusion: Maternal enzyme levels may change with gestational week and as fetal weight increases. It is necessary to differentiate between pathological and physiological changes. These enzymes are also affected by tocolytic agents. Since our study was conducted in a healthy pregnant group without any systemic diseases, we think that the changes caused by gestational age and fetal weight gain are physiologically acceptable. However, any sudden elevation in these enzymes should be thoroughly investigated throughout pregnancy.